Prospect of extracellular vesicles in tumor immunotherapy - Xia, Wenbo; Tan, Yunhan; Liu, Yongen; Xie, Na; Zhu, Huili (Frontiers in Immunology, 2025)
Extracellular vesicles (EVs), as cell-derived small vesicles, facilitate intercellular communication within the tumor microenvironment (TME) by transporting biomolecules. EVs from different sources have varied contents, demonstrating differentiated functions that can either promote or inhibit cancer progression. Thus, regulating the formation, secretion, and intake of EVs becomes a new strategy for cancer intervention. Advancements in EV isolation techniques have spurred interest in EV-based therapies, particularly for tumor immunotherapy. This review explores the multifaceted functions of EVs from various sources in tumor immunotherapy, highlighting their potential in cancer vaccines and adoptive cell therapy. Furthermore, we explore the potential of EVs as nanoparticle delivery systems in tumor immunotherapy. Finally, we discuss the current state of EVs in clinical settings and future directions, aiming to provide crucial information to advance the development and clinical application of EVs for cancer treatment.